The Effectiveness of Using Educational Pillars in Kindergartens and their Impact on Developing Creative Activities among Kindergarten Children in Raising the Marka Brigade - Sarayrah, Amal; Almraiyh, Mahdi Awad; Soub, Tarik Faris Al (Journal of Posthumanism, 2025)
The current research aims to understand the efficiency of using educational pillars in kindergartens and their impact on the development of creative activities among kindergarten children in Liwa Marka education. The research sample included 120 children, male and female, who were purposefully selected from 11 government and private kindergartens in Amman, Marka District, with 60 male and female children from each type of kindergarten (using educational corners and regular kindergartens), where half of the sample was male and the other half was female. A form was prepared to collect data and a field survey was carried out to identify kindergartens that use educational corners. The test of the formal part of the Torrance Test for Creative Thinking was also applied, after extracting the implications of stability and correction stability. After analyzing the data statistically using two-way analysis of variance, the research reached the following results: There are statistically significant differences at the level of (0.01 ≥α) between the average scores of children who attend kindergartens that use educational corners, and the average scores of children who attend regular kindergartens in aspects of developing creative activities, as the results were supportive of the effectiveness of using educational corners in this regard. There are no statistically significant differences at the level of (0.01 ≥α) Gender in all aspects of the development of creative activities, due to gender. There is no statistical effect that is considered significant for the interaction between the variables of kindergarten type and gender in their impact on the development of creative activities. Based on the research results, the researcher presented a number of conclusions and recommendations.